The intermediate filament protein GFAP regulates mitochondrial fission in astrocytes - Ding Xiong; Ye Sing Tan; Fang Yuan; Yinglu Li; Kay En Low; Isabelle Bonne; Sakthikumar Mathivanan; Phil Jun Kang; Zijun Sun; Xueyan Li; Emily Abella; Albee Messing; et al. (Proceedings of the National Academy of Sciences, 2025)
Mitochondrial plasticity, coordinated by fission and fusion, is crucial to ensure cellular functions. Mitochondrial fission is mediated by the GTPase Drp1 at the constriction site, which is proposed to be driven by the actin–myosin contractile force. However, the mechanism that propels constriction remains unclear, and the potential involvement of additional mechanisms in this process remains an open question. Here, using structured illumination microscopy, electron microscopy, and correlative light electron microscopy (CLEM), we show that the type III intermediate filament glial fibrillary acidic protein (GFAP) participates in mitochondria constriction and fission by interacting with Drp1. Remarkably, loss of GFAP results in hyperfused mitochondria under physiological and even Ca 2+ -induced mitochondrial fission conditions. Additionally, mutations in GFAP, the cause of Alexander disease, result in more Drp1 localized to GFAP and lead to significantly increased mitochondrial fissions. Taken together, these findings propose a role of type III intermediate filaments in mitochondrial division.